Impugnação de paternidade : a imprescritibilidade no direito fundamental de filiação - Paiva, Francisca Juliana Castello Branco Evaristo de (2015)
It is a criterious study about the right of parenthood impugnation right by a acknowledged sibling as underage and the possibility that this right comes to be characterized by imprescritibility. The importance is in acknowledge the sonhood right as a fundamental right having by standard only the socioaffectivity. This investigative work has as its objective, to discuss the imprescritibility of the right of impugnation of parenthood of the acknowledged sibling when faced by decisions from the Superior Court of Justice which by itself, only thus acknowledge it, by having the desintegration of a parenthood bonding to consitute another, devaluating the monoparental family. And it was developed from bibliographic research and judged sentences analysis realized by the Superior Court of Justice. As condition to fulfill the intended, in this study was discussed the nowadays Family, as the parenthood and socioaffectivity and the monoparental families, the socioaffectivity and the monoparental families.